A pilot study to measure marks in children with cerebral palsy using a novel measurement template. Issue 6 (15th August 2012) - Bennett, T.; Jellinek, D.; Bennett, M.
Abstract: Aim: The primary aim of this pilot study was to trial a method of assessing bruises in a population of disabled children. If the method was found to be sufficiently robust it would be our intention to undertaking a more extensive observational study. Background: Less is known about normal bruising patterns in children with disability than in those without. It is important that the method used to assess bruising is objective and repeatable. In an effort to define and improve repeatability, we employed a novel bruise measurement template which was printed onto transparent acetate sheets. Method: Twenty primary school age children, the majority of whom were non‐ambulant and severely disabled with cerebral palsy, underwent full skin examination. The template was used to assess any bruises seen. A comparison was then made between measurements made by experienced paediatricians using the template and using a standard tape measure on a series of bruise images in 25 photographs. Results: The majority of children in our pilot were found to have bruises, with one child having 6 and one 7 bruises. This comparative study showed that the two techniques had a very similar precision and that the template was easy to use. Greater precision would require a tighter measurement protocol, whether with a template or a tape measure. Conclusions: Further evaluation of the application of such a template would be worthwhile. We would suggest that our finding of some bruising in this population of disabled children is borne in mind whenever bruising is found in a non‐ambulant child.